PENGARUH AKTIVITAS MENULIS REFLECTIVE JOURNAL DISERTAI CORRECTIVE FEEDBACK TERHADAP HASIL BELAJAR SISWA - Zaxa, Andrius; Djudin, Tomo; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effect of reflective journal writing activity along with corrective feedback on student academic performance in dynamic fluid subject on eleventh grade Pontianak State Senior High School 8. The research method used was an experimental method with quasi-experimental nonequivalent control group design. Intact group random sampling technique was used to select samples from XI MIPA in Pontianak State Senior High School 8, and XI MIPA 4 was chosen as the experimental class while XI MIPA 3 as the control class. Academic performance data were taken using 25 multiple choice questions. Direct instruction learning models are used in both classes, with students in the experimental class given reflective journals (including exercises) as assignment which are accompanied by corrective feedback, while students in the control class are only given the exercises as assignment. Student scores in experimental class at pretest and posttest had average of 27.07 and 64.27, while in control class are 27.73 and 52.13. Asymp. Sig. (2-tailed) U-test (? = 5%) shows that there is a significant difference (0,001) in the posttest scores of students in experimental and control classes, with Cohen?s effect size d value of 1.02 (high category). Keywords: Reflective Journal, Corrective Feedback, Academic Performance, Dinamic Fluids